THE DIAGNOSTIC UTILITY OF FINE NEEDLE ASPIRATION CYTOLOGY (FNAC) IN PALPABLE BREAST LESIONS AT A TERTIARY CARE CENTER - Asmah Afzal; Fatima Khalid; Azra Akhtar; Firdous Iqbal; Uzma Shaheen; Saroash Iqbal (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background and Objective:Breast lesions are among the most common causes of morbidity in women, ranging from benign to malignant conditions. Fine Needle Aspiration Cytology (FNAC) is a widely used diagnostic tool for evaluating palpable breast lesions due to its minimally invasive nature and rapid turnaround time. This study aims to assess the diagnostic utility of FNAC in palpable breast lesions, comparing its accuracy with histopathology.Material & Methods:This retrospective study was conducted at the Department of Pathology, Bahawal Victoria Hospital, Bahawalpur, a tertiary care center, from January 2020 to December 2023. A total of 500 female patients presenting with palpable breast lesions underwent FNAC, followed by histopathological examination where available. Data on patient demographics, FNAC results, and histopathological findings were collected. Statistical analysis was performed to evaluate the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of FNAC.Results:The study included 500 patients, with a mean age of 45.2 ± 12.7 years. FNAC categorized 60% of lesions as benign, 30% as malignant, and 10% as suspicious or inconclusive. Histopathological correlation was available for 300 cases, where FNAC showed a sensitivity of 95%, specificity of 98%, PPV of 97%, and NPV of 96%. The most common benign lesion was fibroadenoma (45%), while invasive ductal carcinoma (IDC) was the predominant malignant lesion (28%). FNAC demonstrated high diagnostic accuracy, particularly in differentiating between benign and malignant lesions.Conclusion:FNAC is a highly effective diagnostic tool for palpable breast lesions, offering excellent sensitivity and specificity. Its minimally invasive nature, combined with rapid results, makes FNAC an invaluable technique in the initial evaluation of breast lesions at tertiary care centers. The study supports the continued use of FNAC as a frontline diagnostic tool, with histopathology reserved for cases requiring further confirmation.